Halide Perovskite Nanocrystal‐Enabled Stabilization of Transition Metal Dichalcogenide Nanosheets (Small 6/2022). Issue 6 (10th February 2022) - Lee, Hyeokjung; Han, Hyowon; Park, Chanho; Oh, Jin Woo; Kim, Hong Hee; Kim, Sohee; Koo, Min; Choi, Won Kook; Park, Cheolmin
Abstract : Photoelectronics In article number 2106035, Cheolmin Park and co‐workers present lanthanide ion‐doped colloidal inorganic halide perovskite nanocrystals as non‐destructive dispersants capable of not only dispersing transition metal dichalcogenide nanosheets in the liquid phase, but also enhancing the photodetection properties of the nanosheets, leading to a high performance near infrared image sensor.